Determination of Sex From Adult Clavicle – An Autopsy based Regional Study (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Studies on “identification of the sex from clavicle bone alone” are carried out by variousworkers all over the world.But, it is well known fact that the racial and geographical differences exist inthe metrical measurement of all the bones including clavicles, as the determination of sex is a populationspecific phenomenon. Matrials and Methode : This study was conducted on100 male clavicles and 100female clavicles collected from identified corpses brought for medicolegal autopsy at Department of ForensicMedicine Govt. Medical College Calicut. Measured the various parameters and compared with previousstudies. RESULTS :In the present study, the length , midclavicular circumference and weight of maleclavicles weres more than female clavicles. The female clavicle has its length around 86% of male clavicleand mean MCC around 83% of the male clavicles.. Robustness index also calculated, mean robustnessindex was 23.11, and could identify only 76 % males and 64% females by this. CONCLUSION:In order toestablish the anthropometric standards, and for the evaluation of the same from time to time, the continuanceof such studies in defined geographical areas over a particular period of time is needed.